Gender Beliefs And Capability Deprivation: A Study Among Indian Women In Penang, Malaysia - Saigaran, Nithiya Guna (2020)
This thesis investigates poor and non-poor Indian women’s gender beliefs and capability deprivation in Penang, Malaysia. The objectives of this study are to identify the most common gender beliefs among poor and non-poor Indian women; determine the levels of capability deprivation of poor and non-poor Indian women; examine the relationship between gender beliefs and capability deprivation and explicate determining factors between gender beliefs and capabilities of poor and non-poor Indian women. Mixed- method design was utilized for this study and data were gathered using survey questionnaires from 300 respondents and in-depth interviews with 24 participants from two districts in Penang: Seberang Perai Tengah and Timur Laut. The findings revealed that the most common gender beliefs of poor and non-poor are traditional beliefs and egalitarian beliefs, respectively. Poor Indian women experienced higher levels of deprivation compared to non-poor Indian women. In addition, there was a positive correlation between gender beliefs and the overall capability deprivation and also with gender beliefs and deprivation of each capability. Four themes were identifiied in explaining the interconnection between gender beliefs and capability deprivation, which are cultural norms, parents as role models, resource allocation among gender and punishments and rewards. This study has expanded the body of knowledge which is much needed by explicating Malaysian Indian women’s deprivation from the gender perspective.